Abraham Maslow's Humanistic Psychology Study on The Character Ale in The Novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna - Fathina Karima Arun; S. Sumiyadi; Rudi Adi Nugroho (Universitas Negeri Semarang, 2025)
This study, entitled “An Analysis of Abraham Maslow's Humanistic Psychology in the Character Ale in Brian Khrisna's Novel Seporsi Mie Ayam Sebelum Mati,” aims to identify the forms of need fulfillment carried out by the main character in accordance with Abraham Maslow's humanistic psychology theory. Maslow's hierarchy of needs includes physiological and psychological needs. Physiological needs include food and drink, clothing, shelter, rest, and sexual needs. Psychological needs include the need for safety, love and belonging, self-esteem, and self-actualization. The method employed in this study is a descriptive qualitative approach, aimed at understanding and describing the phenomenon in depth. The research data sources comprise the dialogues, sentences, phrases, and words of the main character found in the novel Seporsi Mie Ayam Sebelum Mati, published by Gramedia Widiasarana Indonesia (Grasindo) in 2025. The researcher acted as the primary instrument, while data collection was conducted using the read-and-record technique. Based on an analysis of Abraham Maslow's humanistic psychology theory, 30 related data points were identified, indicating that the character Ale made various efforts to fulfill his hierarchy of needs. However, not all of these needs could be fulfilled, particularly the needs for clothing, rest, and sex. Meanwhile, other needs were gradually fulfilled as the story progressed.